2015
DOI: 10.4049/jimmunol.1402770
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Factor H Autoantibodies in C3 Glomerulopathies and in Atypical Hemolytic Uremic Syndrome: One Target, Two Diseases

Abstract: Autoantibodies targeting factor H (FH), which is a main alternative complement pathway regulatory protein, have been well characterized in atypical hemolytic uremic syndrome (aHUS) but have been less well described in association with alternative pathway–mediated glomerulopathies (GP). In this study, we studied 17 patients presenting with GP who were positive for anti-FH IgG. Clinical data were collected and biological characteristics were compared with those of patients presenting with anti-FH Ab-associated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 52 publications
(83 reference statements)
7
91
4
6
Order By: Relevance
“…C3Nef frequently coexists with anti-CFH, possibly having a synergistic effect on AP dysregulation in plasma. In a single report, anti-CFH was also associated with monoclonal Ig (35% cases in the small group of 17 patients), which is in line with previous reports of monoclonal Ig pathogenic involvement in C3G [82,83,99].…”
Section: Acquired Ap Abnormalities In C3gsupporting
confidence: 89%
See 2 more Smart Citations
“…C3Nef frequently coexists with anti-CFH, possibly having a synergistic effect on AP dysregulation in plasma. In a single report, anti-CFH was also associated with monoclonal Ig (35% cases in the small group of 17 patients), which is in line with previous reports of monoclonal Ig pathogenic involvement in C3G [82,83,99].…”
Section: Acquired Ap Abnormalities In C3gsupporting
confidence: 89%
“…In MPGN I patients, Servais et al reported low AP proteins levels, such as C3, CFB, CFH, and CFI (in 46.3, 34.1, 4.9, and 7.3% of cases, respectively) and the prevalence of the C3NeF (in 53.6% cases), what suggested the AP activation [62]. In the other studies, anti-C3b, anti-CFB, and anti-CFH antibodies have been found in Ig-MPGN patients (Table 2) [95,99]. Recent reports have also shown that genetic abnormalities of the AP proteins may be present in immune-complex GN ( Table 1).…”
Section: Immune-complex Glomerulonephritismentioning
confidence: 84%
See 1 more Smart Citation
“…There were no changes in isotype or light chain of the FH autoantibodies over time. Blanc et al described that a restriction of light chains in FH autoantibody positive patients was found in C3 glomerulopathy (C3G), in association with monoclonal gammopathy, but not in autoimmune aHUS (Blanc et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Blanc et al studied FH:autoantibody complexes in the presence of various NaCl concentrations (Blanc et al 2015), but a detailed analysis regarding the avidity profiles and avidity indexes of the FH autoantibodies in serial samples of aHUS patients is currently lacking.…”
Section: Discussionmentioning
confidence: 99%